Intra- And Inter-Group Performance of Oil Producing Countries: A Meta- and Global Frontier Analysis - Gakpey, V.S. (University of Ghana, 2016)
Oil and gas is an important factor in the economic growth and development of most economies and an integral part of the global economy. Oil producing countries (OPCs) play a substantial part in the ownership, production and marketing of extracted hydrocarbons. This has made oil and gas production and supply decisions at the country level key to operations managers globally. To enhance their oil and gas management capabilities, some countries in the international oil industry have coalesced into intergovernmental organisations (IGOs) that are aimed at improving their bargaining powers through consensus and cooperation. However, although these IGOs play an important role in the industry, little is known on the production and supply efficiencies of member states. Based on this background, the study provides insights on the dynamics of intra and inter group performance of OPCs in order to inform operations managers in these countries on their performance and benchmarks in the industry. This was done by assessing performance of OPCs in a particular IGO and comparing their performance with other OPCs in other IGOs. An unbalanced panel of OPCs in four IGOs was used by mainly drawing data from the U.S Energy Information Administration and the World Bank Development Indicators. In all 53 OPCs from the four IGOs in the international oil and gas industry for a 14-year period from 2000 to 2013 were used. Relevant performance measurement techniques in management science and operations management were used. The study identified that the International Energy Agency’s (IEA) production frontier outperforms the production frontiers of the other three IGOs in the inter group performance. IEA, on average, were the best performers followed by the Organization of Arab Petroleum Exporting Countries (OAPEC), Organization of the Petroleum Exporting Countries (OPEC) and the Former Soviet Union (FSU) in that order. Finally, IEA and OAPEC production frontiers were seen to be consistently better than both the OPEC and FSU frontiers for all the 14 years
Thesis (MPhil.)
Keywords: Oil; Countries; Global Frontier Analysis; Ghana